Temporal aspects of wellbeing in later life: gardening among older African Americans in Detroit. Issue 12 (18th December 2020) - Robbins, Jessica C.; Seibel, Kimberly A.
Abstract: Gardening has well-established physical, social and emotional benefits for older adults in varied circumstances. In Detroit, Michigan (United States of America), as in many cities, policy makers, funders, researchers, community organisations and residents regard gardening as a means of transforming bodies, persons, communities, cities and broader polities. We draw on ethnographic research conducted during one gardening season with 27 older African Americans in Detroit to foreground the social dimensions of wellbeing in later life and thus develop a more robust and nuanced understanding of gardening's benefits for older adults. Based on anthropological understandings of personhood and kinship, this article expands concepts of wellbeing to include social relations across multiple scales (individual, interpersonal, community, state) and temporalities (of the activity itself, experiences of ageing, city life). Even when performed alone, gardening fosters connections with the past, as gardeners are reminded of deceased loved ones through practices and the plants themselves, and with the future, through engagement with youth and community. Elucidating intimate connections and everyday activities of older African American long-term city residents counters anti-black discourses of 'revitalisation'. An expansive concept of wellbeing has implications for understanding the generative potential of meaningful social relations in later life and the vitality contributed by older adults living in contexts of structural inequality.